ChemInform Abstract: Fluorodecarboxylation for the Synthesis of Trifluoromethyl Aryl Ethers. Issue 50 (November 2016) - Zhang, Qing‐Wei; Brusoe, Andrew T.; Mascitti, Vincent; Hesp, Kevin D.; Blakemore, David C.; Kohrt, Jeffrey T.; Hartwig, John F.
Abstract: The synthesis of mono‐, di‐, and trifluoromethyl aryl ethers by a newly developed fluorodecarboxylation method is reported.